2013
DOI: 10.1039/c3md20292e
|View full text |Cite
|
Sign up to set email alerts
|

Pseudopeptides with a centrally positioned alkene-based disulphide bridge mimetic stimulate kallikrein-related peptidase 3 activity

Abstract: First successful pseudopeptides of the KLK3-activating bicyclic peptide “C-4” are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This may be caused by the short halflife of the peptides caused by rapid renal excretion and breakdown in plasma by exopeptidases. Therefore, more stable peptide analogs and synthetic peptidomimetics are being developed, in which part of the peptide structure is replaced by building blocks that are resistant to proteolytic breakdown 205,206 . Recently, the first small drug-like molecule Figure 8.…”
Section: Development Of Peptides Modulating the Proteolytic Activity mentioning
confidence: 99%
“…This may be caused by the short halflife of the peptides caused by rapid renal excretion and breakdown in plasma by exopeptidases. Therefore, more stable peptide analogs and synthetic peptidomimetics are being developed, in which part of the peptide structure is replaced by building blocks that are resistant to proteolytic breakdown 205,206 . Recently, the first small drug-like molecule Figure 8.…”
Section: Development Of Peptides Modulating the Proteolytic Activity mentioning
confidence: 99%
“…As the terminal NH 2 group does not seem to be critical for biological activity, analogues 3c and 3d were also included in the series. Replacing the disulfide bridge with a hydrocarbon linker has been reported to considerably increase the in vivo stability and bioavailability of peptides. , A similar alkene linker has already been shown to be a successful disulfide bridge replacement in the other KLK3-stimulating peptide, C-4 . However, in the C-4 peptide, the alkene linker was introduced after the peptide synthesis using a ring-closing metathesis reaction that gave an inseparable mixture of the E - and Z -alkenes.…”
mentioning
confidence: 99%
“…To verify the stereochemistry of the double bond in the purified pseudopeptide 3c , we also analyzed it by NMR using a method we have utilized in a previous study . This showed that the peptide exclusively contained the E- isomer.…”
mentioning
confidence: 99%
See 2 more Smart Citations